The Role of Perceived Social-Emotional Competence in Adolescents’ Mental Health: The Longitudinal Mediating Effect of Peer Relationship and Teacher-Student Relationship - Zhou P; Yan S; Hou L (Psychology Research and Behavior Management)
Ping Zhou,1,2 Sidan Yan,2,3 Lulu Hou2,3 1Shanghai Weiyu High School, Shanghai, 200231, People’s Republic of China; 2Lab for Educational Big Data and Policymaking (Ministry of Education), Shanghai Normal University, Shanghai, People’s Republic of China; 3School of Psychology, Shanghai Normal University, Shanghai, 200234, People’s Republic of ChinaCorrespondence: Ping Zhou, Shanghai Weiyu High School, Shanghai, 200231, People’s Republic of China, Email wypingzhou@163.com Lulu Hou, School of Psychology, Shanghai Normal University, Shanghai, 200234, People’s Republic of China, Email hoululu2020@shnu.edu.cnIntroduction: Perceived social-emotional competence (PSEC) has been identified as a critical factor influencing adolescent mental health. However, limited research has explored the underlying mechanisms linking PSEC to both psychological distress and subjective well-being.Methods: This longitudinal study investigated the associations among PSEC, psychological distress, and subjective well-being, as well as the potential mediating roles of peer relationships and teacher-student relationships. A sample of 452 adolescents (aged 16– 19 years) participated in the study. Structural equation modeling was employed to examine the hypothesized mediation pathways.Results: Correlational analyses showed significant associations among PSEC, subjective well-being, psychological distress, peer relationships, and teacher-student relationships. Longitudinal mediation analyses revealed that the relationship between PSEC and psychological distress was fully mediated by peer relationships. In contrast, the effects of PSEC on subjective well-being were explained by both direct effects and the mediating roles of peer and teacher-student relationships.Discussion: These findings underscore the importance of supportive interpersonal relationships in adolescent mental health. The results suggest that enhancing peer and teacher-student relationships may be a valuable target for interventions aimed at strengthening the positive impact of PSEC.Keywords: perceived social-emotional competence, psychological distress, well-being, relationship with peers and teachers